Pembuatan Aplikasi Peyimpanan Peraturan Perusahaan Berbasis Visual Basic di PT XYZ Divisi HCGS - Maria Karmelita; Harmon Chaniago (BADAN PENERBIT STIEPARI PRESS, 2025)
The utilization of information technology in the digital era is an important factor in supporting company operational activities, including in managing regulatory data. PT XYZ Human Capital General Support (HCGS) Division currently still uses an ordinary excel-based regulatory data storage system that only contains links to external websites and for internal regulations originating from within the company. This system has several disadvantages, such as dependence on internet connection, risk of unavailability of documents when needed, and lack of effectiveness in searching data and documents. Regulations fall into the category of vital archives, thus requiring a structured and reliable management system. This project aims to design an excel VBA-based company regulation data storage and management application to increase the effectiveness and ease of access to documents. Tests were carried out using the black box testing method and distributing questionnaires with evaluation indicators, referring to the five aspects of usability testing, namely learnability, efficiency, memorability, errors, satisfaction. The evaluation results show that this application has met user needs and functions as expected. The results of this project are expected to provide benefits for both the author, company, and academic parties as an applicable and sustainable digital solution.